2016
DOI: 10.1111/jfpp.12810
|View full text |Cite
|
Sign up to set email alerts
|

Rheology Study on Low-Sugar Apple Jam by a New Nonlinear Regression Method of Herschel-Bulkley Model

Abstract: Structure break was found in shearing process of static prepared low‐sugar apple jam, which is a thixotropic and shear‐thinning fluid. In order to investigated this jam, a new nonlinear regression method of Herschel–Bulkley (H‐B) model without measuring yield stress was set up using R2 as optimizing criterion, and compared with Casson model. Dynamic yield stress was calculated using the regression of downward curve. Casson model was found fit in high shear rate (in one case, R2 0.9986, still lower than H‐B mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
(93 reference statements)
0
9
0
Order By: Relevance
“…The flow index is a parameter that expresses the internal structure of food fluids (Guo et al., 2017). n indicates fluid deviation from Newtonian behavior.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The flow index is a parameter that expresses the internal structure of food fluids (Guo et al., 2017). n indicates fluid deviation from Newtonian behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Also, according to the flow curves, it was found that the samples with higher sucrose concentration and TSS value have higher viscosity. Shear-thinning behavior was also observed in the jam of other fruits such as mango (Basu & Shivhare, 2010), apple (Guo et al, 2017), and gabiroba (Barbieri et al, 2018), which is determined by the flow curve. Herschel-Bulkley model was appropriate for the rheological behavior described by the flow curves, and the value of R 2 for it was 0.996, which is similar to the results of mango jam (Basu & Shivhare, 2010), with R 2 values between 0.818 and 0.996 and apple jam (Guo et al, 2017), with R 2 values from 0.891 to 0.998.…”
Section: Steady-state Rheologymentioning
confidence: 87%
See 1 more Smart Citation
“…The Herschel-Bulkley model is adopted in the present work to study multiphase flow. This model is widely used in different fields [35][36][37][38] and can be expressed as:…”
Section: Governing Equationsmentioning
confidence: 99%
“…Both equations (2.12) and (2.14) are shown to represent shear thinning behaviour of food products very well [32]. A plot of the above non-Newtonian models is visible in Fig.…”
Section: Non-newtonian Models (Shear-dependence)mentioning
confidence: 82%